Tacrolimus trough level and oxidative stress in Tunisian kidney transplanted patients - Mariam Ammar; Soumaya Yaich; Ahmed Hakim; Hanen Ghozzi; Zouheir Sahnoun; Mohamed Ben Hmida; Khaled Zghal; Lobna Ben Mahmoud (Renal Failure)
Background The effect of tacrolimus (TAC) on oxidative stress after kidney transplantation (KT) is unclear. This study aimed to evaluate the influence of TAC trough levels of oxidative stress status in Tunisian KT patients during the post-transplantation period (PTP).Methods A prospective study including 90 KT patients was performed. TAC whole-blood concentrations were measured by the microparticle enzyme immunoassay method and adjusted according to the target range. Plasma levels of oxidants (malondialdehyde (MDA) and advanced oxidation protein products (AOPP)) and antioxidants (ascorbic acid, glutathione (GSH), glutathione peroxidase (GPx), and superoxide dismutase (SOD)) were measured using spectrophotometry. The subjects were subdivided according to PTP into three groups: patients with early, intermediate, and late PT. According to the TAC level, they were subdivided into LL-TAC, NL-TAC, and HL-TAC groups.Results A decrease in MDA levels, SOD activity, and an increase in GSH levels and GPx activity were observed in patients with late PT compared to those with early and intermediate PT (p < 0.05). Patients with LL-TAC had lower MDA levels and higher GSH levels and GPx activity compared with the NL-TAC and HL-TAC groups (p < 0.05).Conclusion Our results have shown that in KT patients, despite the recovery of kidney function, the TAC reduced but did not normalize oxidative stress levels in long-term therapy, and the TAC effect significantly depends on the concentration used.